Enoxaparin for outpatients with COVID-19: 90-day results from the randomised, open-label, parallel-group, multinational, phase III OVID trial : full-length article - Voci, Davide; Götschi, Andrea; Held, Ulrike; Bingisser, Roland; Colucci, Giuseppe; Dürschmied, Daniel; Fumagalli, Riccardo M.; Gerber, Bernhard; Hasse, Barbara; Keller, Dagmar I.; Konstantinides, Stavros V.; Mach, François; et al. (Thrombosis research, 2023)
Introduction - The benefits of early thromboprophylaxis in symptomatic COVID-19 outpatients remain unclear. We present the 90-day results from the randomised, open-label, parallel-group, investigator-initiated, multinational OVID phase III trial. - Methods - Outpatients aged 50 years or older with acute symptomatic COVID-19 were randomised to receive enoxaparin 40 mg for 14 days once daily vs. standard of care (no thromboprophylaxis). The primary outcome was the composite of untoward hospitalisation and all-cause death within 30 days from randomisation. Secondary outcomes included arterial and venous major cardiovascular events, as well as the primary outcome within 90 days from randomisation. The study was prematurely terminated based on statistical criteria after the predefined interim analysis of 30-day data, which has been previously published. In the present analysis, we present the final, 90-day data from OVID and we additionally investigate the impact of thromboprophylaxis on the resolution of symptoms. - Results - Of the 472 patients included in the intention-to-treat population, 234 were randomised to receive enoxaparin and 238 no thromboprophylaxis. The median age was 57 (Q1-Q3: 53-62) years and 217 (46 %) were women. The 90-day primary outcome occurred in 11 (4.7 %) patients of the enoxaparin arm and in 11 (4.6 %) controls (adjusted relative risk 1.00; 95 % CI: 0.44-2.25): 3 events per group occurred after day 30. The 90-day incidence of cardiovascular events was 0.9 % in the enoxaparin arm vs. 1.7 % in controls (relative risk 0.51; 95 % CI: 0.09-2.75). Individual symptoms improved progressively within 90 days with no difference between groups. At 90 days, 42 (17.9 %) patients in the enoxaparin arm and 40 (16.8 %) controls had persistent respiratory symptoms. - Conclusions - In adult community patients with COVID-19, early thromboprophylaxis with enoxaparin did not improve the course of COVID-19 neither in terms of hospitalisation and death nor considering COVID-19-related symptoms.
Online verfügbar: 12. November 2022, Artikelversion: 22. Dezember 2022
Gesehen am 10.09.2024